Management of heart failure patients with systolic dysfunction in a real world setting-a physician-based survey - Sawhney, J. P.; Jain, Peeyush; Kantanavar, Kiran (International Journal of Advances in Medicine, 2023)
Background: The objective of this study was to understand cardiologists’ perspectives on heart failure (HF) management with an emphasis on heart rate (HR) optimization and practice patterns among different medical specialties. Methods: A digital, cross-sectional, questionnaire-based survey involving 149 Indian cardiologists who were experienced in the management of patients with HF in their clinical practice was conducted. The survey questionnaire included 53 items divided into five sections. Responses were analyzed and data were represented as summary statistics. Results: According to most cardiologists, majority of patients belong to the New York Heart Association (NYHA) categories II and III, with ischemia being the most prevalent cause of HF. For patients with HF with reduced ejection fraction (HFrEF), HR>70 beats per minute and sinus rhythm, 38.9% of clinicians strongly agreed to include ivabradine in the treatment regimen. According to 56.4% of clinicians, 26%-50% of patients with HFrEF were receiving ivabradine therapy at <50% guideline-directed target dose of β-blockers. At the highest therapeutic dosage of ivabradine, 46.3% of clinicians noticed a 6-10 bpm reduction in HR. Additionally, it was reported that a stable HFrEF patient consumed an average of 4-6 tablets daily (67.1%), which increased the pill burden. Overall, 58.4% and 67.1% of clinicians strongly believed that cutting back on medications will assist with therapy adherence and that improved therapy adherence and compliance aid with clinical outcomes, respectively. Majority of the clinicians strongly agreed or agreed that patients should be switched from twice-daily to once-daily ivabradine. Conclusions: Clinical outcomes of patients with HF could be improved by reducing the pill burden and improving compliance.